Unfunded pension systems : ageing and migration - Uebelmesser, Silke (Amsterdam ; London : Elsevier, 2004)
Pension systems in most industrialised countries are unfunded, i.e. they are pay-as-you-go financed and thus depend on a well-balanced ratio (old) recipients to (young) contributors. This so-called dependency ratio will worsen significantly in the next few decades due to two developments: ageing of the population and increased labour mobility.This book analyses the viability of unfunded pension systems in the presence of the projected demographic evolution. The analysis focuses on questions concerning a) efficiency considerations and the possibility of welfare improvements; b) political economy aspects and the feasibility of reforms; c) the process of European integration and its influence on national pension systems. The theoretical analysis is complemented in numerous ways by quantitative parts and institutional details.
Includes bibliographical references and index.
rpm 22/09/16, ijb 19/03/2019
Loans
Keywords: Pensions; Emigration and immigration; Demographic transition; Politics & government ; Welfare & benefit systems; BUSINESS & ECONOMICS -- Personal Finance -- Retirement Planning